2020
DOI: 10.3390/vaccines8010108
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Seasonal Influenza Virus Activity in a Subtropical City in China, 2013–2019

Abstract: Background: To optimize seasonal influenza vaccination programs in regions with potentially complicated seasonal patterns, the epidemiological characteristics of seasonal influenza activity in a subtropical city of China were explored. Materials and Methods: Influenza virus data of patients with influenza-like illness (ILI) during 2013-2019 were collected from two sentinel hospitals in a subtropical region of China, Yichang city. The influenza virus positive rate among sampled ILI cases served as a proxy to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The start of an influenza epidemic period was defined as the first week during which the positive rate of influenza virus testing was higher than 10% and stayed above that level for at least four consecutive weeks. The end of an influenza epidemic period was defined as the first week during which the positive rate was lower than 10% and stayed at that level for at least four consecutive weeks 19 . Based on influenza activity, climate, and geography, we divided China into two distinct regions, north and south, for the analysis and interpretation of influenza surveillance data.…”
Section: Discussionmentioning
confidence: 99%
“…The start of an influenza epidemic period was defined as the first week during which the positive rate of influenza virus testing was higher than 10% and stayed above that level for at least four consecutive weeks. The end of an influenza epidemic period was defined as the first week during which the positive rate was lower than 10% and stayed at that level for at least four consecutive weeks 19 . Based on influenza activity, climate, and geography, we divided China into two distinct regions, north and south, for the analysis and interpretation of influenza surveillance data.…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, children aged 5–14 years had the highest proportion of positive influenza specimens (36.33%) among all age groups, which was consistent with previous studies. 12–15 This phenomenon may stem from the majority of children aged 5–14 years being students who attend school in densely populated classrooms with limited ventilation, have poor hygiene and disease prevention awareness, and are more susceptible to influenza transmission due to their young age and weak immunity, leading to a high incidence of influenza. Therefore, influenza prevention and control measures should be prioritized at the levels of schools and childcare institutions, with a focus on strengthening health education and implementing effective protective measures including targeted influenza vaccination campaigns.…”
Section: Discussionmentioning
confidence: 99%
“… 26–29 Our results showed that influenza epidemics in Chongqing tend to occur in spring and winter but influenza B viruses were primarily dominant in the spring season. 10 , 12 During this period, the public should pay attention to non-pharmaceutical prevention measures, such as washing hands, wearing masks, opening windows for ventilation frequently.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism will provide innovative models and standards for other regions to conduct disease surveillance and issue early warnings. 24 , 25 …”
Section: Vaccine and Public Health Sub-sessionmentioning
confidence: 99%